Optimalisasi Literasi Digital dalam Memilih Bahan Makanan untuk Mencegah Stunting - Agung Hartadi; Muhammad Isnaini Fatoni; Nurhadi Nugroho; Purwanta; Endah Wening Budiningrum (Sekolah Tinggi Ilmu Bisnis Kumala Nusa, 2024)
The results of the Recapitulation of the Monitoring of Nutritional Status (PSG) of Toddlers TB/U Bantul Regency in February 2023 (Bantul, 2023), explained that there were 54 toddlers experiencing stunting or 7, 84%. Stunting occurs due to poor parenting, which occurs not only because of economic inability but also due to lack of time for parents to care because they are busy working. In addition, variations in feeding also affect children's appetite for healthy food. This is what happened in Kayen Hamlet Sendangsari Pajangan Bantul DIY. Improving parenting can be done by providing additional insight into good parenting. This increase in knowledge can be done through information sources that can be obtained easily, namely mobile phones. The utilization of mobile phones in finding information on childcare to prevent stunting is not widely known by mothers. Searching for information through Google, social media can be done by typing keywords, using tabs, quotation marks, dashes, has tags or hashtags #. This can be done with digital literacy through digital education. With increased digital literacy in choosing food ingredients, mothers can make better decisions about children's nutrition, which in turn helps prevent stunting and supports optimal growth and development of children.